The PADME detector. (22nd September 2021) - Alexander, J; Bossi, F; Buonomo, B; Capirossi, V; Caricato, A P; De Sangro, R; Di Giulio, C; Domenici, D; Ferrarotto, F; Finocchiaro, G; Fiore, S; Foggetta, L G; et al.
Abstract: To search for the production of a dark photon ( A ′ ) in the process e + e − → A ′ γ, the PADME apparatus has been built athe INFN Laboratori Nazionali di Frascati. It is a small-scale detector consisting of an active target, a beam monitor system, a spectrometer to measure charged particle momenta in the range 50–400 MeV, a dipole magnet to deflect the primary positron beam out of the spectrometer and allow charged particle momentum analysis and an electromagnetic calorimetric system to detect signal and background photons produced in the annihilations with high accuracy. Each element has specific requirements that are stringent and sometimes at the limit of present technology. This proceeding will give an overview of each component and a description of the technical solutions implemented to accomplish the experiment needs. Results of the commissioning data taking, performed from October 2018 to February 2019, will be illustrated.